Genetic variability and differentiation among polymorphic populations of the genusSynoicum(Tunicata, Ascidiacea) from the South Shetland Islands - Wiernes, María Paula; Sahade, Ricardo Jose; Tatian, Marcos; Chiappero, Marina Beatriz (Polar Biology)
In Antarctica, ascidians are among the most conspicuous and abundant organisms in benthic ecosystems and many species present wide distribution patterns. Two similar forms of ascidians of the colonial genus Synoicum were sampled along the South Shetland Islands, one greenish-yellow with elongated colony stalks and the other yellow-orange with shorter stalks and more rounded colony bodies. The taxonomic analyses indicated that the greenish-yellow form corresponded to the description of the species S. ostentor and the yellow-orange form to that of S. adareanum. However, molecular analyses using the cytochrome oxidase I gene did not detect clear differences between both forms. The frequency and geographic distribution of haplotypes indicate that some degree of gene flow may be occurring, strongly suggesting that both morphotypes did not achieve a complete reproductive isolation yet, that they can still interbreed and should therefore be considered as a single species. Surprisingly, these results are not in line with recent studies of Antarctic fauna using a similar approach, which revealed several cases of morphologically indistinguishable but genetically distinct species. Fil: Wiernes, María Paula. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Centro Cientifico Tecnologico Cordoba. Instituto de Diversidad y Ecologia Animal; Argentina. Universidad Nacional de Cordoba. Facultad de Cs.exactas Fisicas y Naturales. Departamento de Diversidad Biologica y Ecologica. Cat.de Ecologia Marina; Argentina Fil: Sahade, Ricardo Jose. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Centro Cientifico Tecnologico Cordoba. Instituto de Diversidad y Ecologia Animal; Argentina. Universidad Nacional de Cordoba. Facultad de Cs.exactas Fisicas y Naturales. Departamento de Diversidad Biologica y Ecologica. Cat.de Ecologia Marina; Argentina Fil: Tatian, Marcos. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Centro Cientifico Tecnologico Cordoba. Instituto de Diversidad y Ecologia Animal; ...